Health services utilization during terminal illness in Addis Ababa, Ethiopia - Reniers, Georges (Oxford University Press, 2009)
Objectives We describe modern and alternative health services use in terminal illness of adults, and assess whether utilization patterns of TB/AIDS patients are distinct from those of patients suffering from other illnesses. Methods Data are from post-mortem interviews with close relatives or caretakers of the deceased. We provide descriptive statistics of health care utilization in adults and discuss their covariates in multivariate analyses. Results Over 85% of terminally sick patients visited a modern medical facility, but less than 40% spent more than 24 hours in a medical facility and only 25% died in one. Traditional healer (11%) and holy water (46%) visits offer a common treatment and healing alternative, but these visits do not co-vary in any consistent manner with the utilization of modern medical services. In terms of the cause of death, we find a higher contact rate with both modern and alternative medical service providers among TB/AIDS patients compared with those suffering from other medical conditions. The duration of illness seems to account for a good share of that variability. Other covariates of health services utilization are socio-economic status, education and age. Conclusions The contact rate of adults with modern medical facilities in terminal illness is almost universal, but their usage intensity is rather low. Alternative curative options are less commonly used, and do not exclude modern health services use. This suggests that both types of services are considered complements rather than alternatives for each other. Because the contact rate with health service providers is greatest for TB/AIDS patients, it is unlikely that HIV/AIDS-related stigma is an impediment to seeking care. We cannot exclude, however, that it delays health-seeking behaviour.